The relationship to age and cerebral vascular accidents of fibrin and fibrinolytic activity - Hume, R. (1961)
Three `normal' groups of people—young, middle-aged, and old—have been investigated with regard to the fibrin content and fibrinolytic activity of the blood. The fourth group consisted of middle-aged people who had previously sustained a cerebral vascular accident matched statistically for age with the middle-aged normals. It was concluded that fibrin increases with age but there is an interaction between age and sex, the female having a higher level in the young group and the male a higher level in the middle-aged group. There was no sex difference in the levels of fibrin in the old age group. Fibrinolytic activity increases with age and there is a positive correlation between fibrin and fibrinolytic activity but no age-sex interaction. Those with cerebral vascular accidents tended to have higher fibrin levels and lower fibrinolytic activity but the differences were not statistically significant. There did, however, appear to be an increase in antifibrinolytic activity in the cerebral vascular group.